Edukasi Keselamatan Berkendara Berbasis Data Survei: Upaya Pencegahan Perilaku Berisiko di Kecamatan Bengkalis - Wahab, Wahyuni; Hamidatul Aminah (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2025)
Traffic safety is a serious issue that directly impacts the security and well-being of the community, including in Bengkalis District. A survey involving 42 respondents from various age groups and backgrounds identified a number of risky driving behaviors, such as non-compliance with helmet use, high-speed driving, and negligence when crossing intersections. This data served as the basis for implementing a community service program focused on preventing risky behavior on the road. The program was designed with a data-driven approach that took into account local conditions and the behavioral characteristics of the local community. The implementation team designed and implemented an interactive educational session attended by 40 participants, consisting of motorcycle riders, students, and local community members. The educational materials included theoretical explanations, visual simulations, group discussions, and case studies relevant to the situation on the ground. This method aimed not only to convey information but also to build critical awareness regarding the risks and consequences of unsafe driving behavior. The results showed an increase in participants' understanding of traffic safety regulations and the importance of complying with safety signs and procedures. Several participants reported changes in attitudes, such as a commitment to always wear a helmet and reduce speed when driving. These findings indicate that relevant, participatory, and community-based educational interventions can be an effective first step in shaping safer driving behaviors. The program's sustainability is expected to be achieved through collaboration with schools, community organizations, and local government agencies, as well as the integration of traffic safety materials into educational curricula and community activities. This approach has the potential to create a culture of safe, disciplined, and sustainable driving in Bengkalis District, while also serving as a model intervention that can be replicated in other areas with similar challenges.